2014
DOI: 10.1021/ja500356z
|View full text |Cite
|
Sign up to set email alerts
|

Guest Molecule-Responsive Functional Calcium Phosphonate Frameworks for Tuned Proton Conductivity

Abstract: We report the synthesis, structural characterization, and functionality (framework interconversions together with proton conductivity) of an open-framework hybrid that combines Ca(2+) ions and the rigid polyfunctional ligand 5-(dihydroxyphosphoryl)isophthalic acid (PiPhtA). Ca2[(HO3PC6H3COOH)2]2[(HO3PC6H3(COO)2H)(H2O)2]·5H2O (Ca-PiPhtA-I) is obtained by slow crystallization at ambient conditions from acidic (pH ≈ 3) aqueous solutions. It possesses a high water content (both Ca coordinated and in the lattice), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 70 publications
9
132
2
1
Order By: Relevance
“…Above this temperature, a drop in conductivity is observed as is typical for many water-mediated proton conductors that undergo dehydration at elevated temperatures. 7,8,17 This is supported by impedance measurements performed under varying humidity conditions ( Figure S4). At 70°C, the conductivity val- Figure 2.…”
Section: Supporting Informationsupporting
confidence: 54%
See 1 more Smart Citation
“…Above this temperature, a drop in conductivity is observed as is typical for many water-mediated proton conductors that undergo dehydration at elevated temperatures. 7,8,17 This is supported by impedance measurements performed under varying humidity conditions ( Figure S4). At 70°C, the conductivity val- Figure 2.…”
Section: Supporting Informationsupporting
confidence: 54%
“…19 Cabeza et al recently reported an alkaline earth metal phosphonocarboxylate MOF, CaPiPhtA, which possesses a pillared layered structure in which monoprotonated phosphonic acid groups protrude into inter-layer spaces. 17 20 a MIL-101 framework whose pores were loaded with H 2 SO 4 , which exhibits a conductivity of 6.0×10 -2 S.cm -1 at 80°C and 20%RH.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The smaller p K a value of H 2 PO 4 − (7.2) than H 2 BO 3 − (12.74) results in more than one order of magnitude higher conductivity for NDTBP than NDTB. Such high proton conductivities of CEFs, especially for NDTBP, are comparable to the most efficient MOF counterparts, such as PCMOF‐3 (3.5×10 −5 S cm −1 at 25 °C and 98 % RH),11d ZPGly (1×10 −3 S cm −1 at 140 °C and 95 % RH),18 Ca‐PiPhtA‐NH 3 (6.6×10 −3 S cm −1 at 24 °C and 98 % RH),19 PCMOF2 1/2 (2.1×10 −2 S cm −1 at 85 °C and 90 % RH) ,[11b] PCMOF10 (3.55×10 −2 S cm −1 at 70 °C and 95 % RH),13 CPM‐103a (5.8×10 −2 S cm −1 at 22.5 °C and 98 % RH),14 and UiO‐66(SO 3 H) 2 (8.4×10 −2 S cm −1 at 80 °C and 90 % RH) 12…”
mentioning
confidence: 91%
“…Chociaż prace badawcze nad obecnymi na rynku wodorowymi ogniwami paliwowymi nie są zakończone, to podjęcie badań nad rozwojem idei ogniwa paliwowego zasilanego węglem brunatnym jest interesujące [49]. Realizowane są również badania materiałowe nad nowymi krystalicznymi ciałami stałymi typu MOF, posiadającymi zdolność przewodzenia protonów w podwyższonej temperaturze [3]. Projektowanie i konstrukcja magnesów nadprzewodzących będących źródłem bardzo silnych pól magnetycznych jest również aktualnym wyzwaniem [36,47].…”
Section: Wybrane Przykłady Konwersji Energiiunclassified